Hot mix asphalt (HMA) properties using natural rubber latex (NRL)-modified bitumen - Shafii, Mohd Amin; Chia, Sian Jiun; Rais, Nuryantizpura Mohamad (International Journal of Engineering and Technology, 2018)
Hot mix asphalt (HMA) is one of the common flexible pavement used in Malaysia. Due to the increasing in the volume of traffic nowadays, unmodified HMA has begun to be insufficient in providing the strength to resist the increased traffic load. Therefore, many research have been done to improve HMA by modifying the bitumen. This study aims to investigate the properties of the HMA using natural rubber latex (NRL) modified bitumen. The optimum bitumen content (OBC) of the NRL-Modified HMA was determined by using Marshall mix design method and the properties of the NRL-Modified HMA was investigated based on the strength and volumetric properties. Besides that, a few tests were conducted in order to determine the properties of the bitumen and aggregates used. The properties of bitumen determined based on its softening point, ductility and penetration while the properties of the aggregated were determined based on its apparent specific gravity, aggregate impact value and shape (flakiness index and elongation index). From the result, it was found that the addition 9% of NRL by the total weight of modified bitumen had altered the volumetric properties and decrease the strength properties of the HMA.